In Vitro Plant Regeneration Of Grape Cv. ‘red Globe’ Through Direct Organogenesis (Applied Biological Research, 2023)
A study was conducted to develop a protocol for in vitro plant regeneration in grape cv. ‘Red Globe’ via nodal segments and shoot tips. The surface sterilization  treatment-combination of 0.5% carbendazim (30 min) + 0.5% NaOCl (10 min)  + 70% ethanol (30 sec) was most effective for nodal segments with highest  survival rate of 68.33%. For shoot tips the treatment with 0.3% carbendazim  (30 min) + 0.25% NaOCl (10 min) + 70% ethanol (30 sec) was found favourable.  MS medium supplemented with 2.0 mg L-1 BAP was optimum for initial culture  establishment of both the explants. However, MS medium supplemented with  2.0 mg L-1 BAP and 0.2 mg L-1 NAA resulted in the highest proliferation rate in  both explants and the treatment was used for subsequent subcultures for shoot  elongation. For in vitro rooting, 2 mg L-1 IBA + 200 mg L-1 activated charcoal  was optimum with highest response of 85.96% and 5.1 roots shoot-1. The highest  ex vitro survival percentage of plantlets (72.84%) was obtained with a hardening  media of pot mix and vermicompost (1:1).
Keywords: Grapes; nodal segments; plant regeneration; Red Globe; shoot tips